Conquering the obstacles during the intervention of a proximal chronic total occlusion of right coronary artery with a concurrent significant ostial stenosis: a case report - Muhammad Insani Ilman; Yudi Her Oktaviono; Mohammad Budiarto; Suryo Ardi Hutomo; Ryan Enast Intan (Journal of the Pakistan Medical Association, 2024)
Percutaneous coronary intervention (PCI) on a proximal chronic total occlusion (CTO) of the right coronary artery (RCA) with concurrent ostial stenosis can be challenging because of the significant difficulty in properly engaging the catheter and providing stable support during the procedure. We report the case of a 57-year-old man with chronic coronary syndrome who underwent an elective PCI at the Dr. Soetomo General Hospital in Surabaya, on April 13th, 2022. At the beginning of the procedure, there was difficulty in intubating the RCA, which required the guide catheter replacement. The angiography revealed a significant lesion at the ostium, a CTO at proximal to mid- RCA with bridging collaterals, and a significant distal lesion. Several strategies to improve guiding catheter support during PCI are using large and supportive shape guide catheters, deep guide catheter intubation, extra support wire, microcatheter and guide catheter extension. The risk of pressure dampening and ischaemia upon engagement should always be kept under consideration. Keywords: Percutaneous, Coronary Intervention, Catheters, Vascular Diseases, Ischemia, Angiography, Intubation, Intratracheal